Digital first impressions: how personal branding on social platforms drives person–organization fit in Surabaya - Vonni Meyra Sutikno; Daniel Joel Immanuel Kairupan (Jurnal Mantik, 2026)
Social media is an important element in the digital recruitment process. Digital recruitment no longer only means recruiters assessing applicants, but also developing its function for applicants to do personal branding and assess companies. The urgency of this research arises because there is a need to understand how job applicants behave and market themselves on social media and how it affects person-organization fit in the company. This research aims to fill the research gap by knowing the digital behavior of job applicants in building personal branding on social media and its impact on the perception of the fit of their own values with the intended company. This research method uses a quantitative approach with a survey method. Sampling was carried out using the purposive sampling technique to 200 job applicants in the city of Surabaya who had or were applying for jobs and were actively using professional social media such as LinkedIn. The analysis was carried out with SPSS through validity and reliability tests, descriptive analysis, Pearson correlation, and multiple linear regression. This research is expected to make a theoretical and practical contribution in understanding the influence of personal branding development on the Person-Organization Fit felt by applicants in digital recruitment. In addition, the results of this research are also expected to be a reference in the development of effective personal branding strategies for applicants as well as social media-based employer branding and digital recruitment strategies for companies